Spatial landscape patterns and trends of declining reed-beds in peninsular Italy. (4th May 2019) - Lastrucci, L.; Cerri, M.; Coppi, A.; Dell'Olmo, L.; Ferranti, F.; Ferri, V.; Filipponi, F.; Foggi, B.; Galardini, R.; Reale, L.; Venanzoni, R.; Viciani, D.; et al.
Abstract: Patterns and trends of declining reed-beds in four freshwater ecosystems in central Italy are investigated through an aerial orthoimagery-based diachronic analysis over a period of 24 years. Extent variations and retreat from the waterfront are detected in all sites, compensated only in few cases by backwards enlargements. These shape and size modifications suggest that reed die-back is associated with retreat and with a notable fragmentation process. Long-term analysis performed in one of the sites, compared to water levels, shows a drastic extent decrease co-occurring with an artificial rise of the water level, confirming the regulation of freshwater bodies as a driver of biodiversity loss. Results also suggest that reed-dominated ecosystems may reach a threshold of tolerance towards stressing conditions beyond which they cannot regenerate. The carried out study testifies for a valuable role of landscape metrics in analysing the spatial processes related to declining reed-beds. Spatial metrics prove to be a suitable tool in monitoring processes, working as early warning signals of ongoing decline and helping to model future changes.